Useful plants of the flora of Aktobe region - Aipeisova, S.A.; Utarbaeva, N.A.; Kazkeev, E.T. (Fundamental and Experimental Biology, 2019)
In the article the results of long-term studies of useful plants of Aktobe region were presented, which is particularly interesting in terms of the botanical and geographical location. This region is located at the boundary between Europe and Asia. Seven groups of useful plants were identified: forage, medicinal, food, meadow, technical, ornamental, poisonous. According to the results of research, 876 species, which possess certain prop-erties used by humans, have been identified in the region. It constitutes 59.4 % of the total number of flora species in Aktobe region. It was revealed that the largest number of species are presented in the following groups: medicinal plants — 593 species (40.2 %), forage plants — 428 species (29 %), ornamental — 253 spe-cies (17.2 %) of the region’s flora. The smallest group are poisonous plants — 114 species. Many species have complex utility value. The most common species are in Aktobe region, such as: Agropyron cristatum, Bromopsis inermis, Eremopyrum orientale, Festuca valesiaca, Phleum phleoides, Poa pratensis, etc. Agropyron cristatumand Secale sylvestremay be of interest for breeding.